Different Modulating Effects of Adenosine on Neonatal and Adult Polymorphonuclear Leukocytes. (1st August 2012) - Hou, Pei-Chen; Yu, Hong-Ren; Kuo, Ho-Chang; Wang, Lin; Lin, Li-Yan; Sheen, Jiunn-Ming; Hsu, Te-Yao; Ou, Chia-Yu; Jheng, Yi-Jyun; Yang, Kuender D.; Cheng, Wen-Hsin
Abstract : Polymorphonuclear leukocytes (PMNs) are the major leukocytes in the circulation and play an important role in host defense. Intact PMN functions include adhesion, migration, phagocytosis, and reactive oxygen species (ROS) release. It has been known for a long time that adenosine can function as a modulator of adult PMN functions. Neonatal plasma has a higher adenosine level than that of adults; however, little is known about the modulating effects of adenosine on neonatal PMNs. The aim of this study was to investigate the effects of adenosine on neonatal PMN functions. We found that neonatal PMNs had impaired adhesion, chemotaxis, and ROS production abilities, but not phagocytosis compared to adult PMNs. As with adult PMNs, adenosine could suppress the CD11b expressions of neonatal PMNs, but had no significant suppressive effect on phagocytosis. In contrast to adult PMNs, adenosine did not significantly suppress chemotaxis and ROS production of neonatal PMNs. This may be due to impaired phagocyte reactions and a poor neonatal PMN response to adenosine. Adenosine may not be a good strategy for the treatment of neonatal sepsis because of impaired phagocyte reactions and poor response.